Оценка вероятности возникновения гидродинамических аварий при каскадном расположении водохранилищ - Levkevich Виктор; Pastukhov Сергей; Mil’man В. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
The methodology for assessment of the hydrodynamic disaster probability on artificial water objects of Republic of Belarus has been presented. It has been developed on the basis of the fault-tree analysis method. The methodology considers natural and anthropogenic risk factors effects on the artificial water objects; the tandem and isolated reservoirs arrangement has been considered as well. The probability calculation results for hydrodynamic disaster of Svisloch tandem reservoir system have been presented. The developed methodology can be applied for hydrodynamic disaster probability assessment as well as for short-term and long-term prognoses.